2017
DOI: 10.18502/kls.v2i6.1029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus megaterium and Bacillus mycoides Bacteria as Probiotic Bacteria in Fish and Shrimp Feed

Abstract: This study was aimedto identify probiotic characteristics and to test the cellulolytic ability of Bacillus megaterium and Bacillus mycoides bacteria for probiotic microbe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
5
12
0
Order By: Relevance
“…The results were similar to the results of Andriani et al, 2017, they stated that Bacillus megaterium are concave, smooth and milk white. Our results were parallel with the studies of Bhattacharyya et al, 2016 they stated that Potash mobilizing isolates were gram negative, rod-shaped, motile and creamish in appearance.…”
Section: Morphological Characterizationsupporting
confidence: 88%
“…The results were similar to the results of Andriani et al, 2017, they stated that Bacillus megaterium are concave, smooth and milk white. Our results were parallel with the studies of Bhattacharyya et al, 2016 they stated that Potash mobilizing isolates were gram negative, rod-shaped, motile and creamish in appearance.…”
Section: Morphological Characterizationsupporting
confidence: 88%
“…Findings in this study were similar to that of Neethu et al [ 43 ] where 3000 μg/l of Pb was identified as the range of concentration that inhibited bacterial growth. Similarly, studies by Andriani et al [ 52 ] reported the isolation of different bacterial species such Bacillus sp. and Enterococcus sp.…”
Section: Discussionmentioning
confidence: 89%
“…From macroscopic and microscopic observations and biochemical tests, it is shown that B. megaterium is concave, smooth, and milkwhite. The cell morphology shows that the cell is rodshaped, Gram-positive, and sporous (Andriani et al 2017). Some B. megaterium proteins are very important in the food industry and pharmacy.…”
Section: Bacillus Megaterium (Fin 2)mentioning
confidence: 99%
“…B. megaterium secretes a variety of enzymes, ranging from amylases used in the bakery industry to penicillin amidase used to manufacture new synthetic antibiotics (Mobitec 2008). B. megaterium can also produce several other enzymes, such as mutarotase, glucose dehydrogenase, -galactosidase, and cellulose (Andriani et al 2017).…”
Section: Bacillus Megaterium (Fin 2)mentioning
confidence: 99%